Persepsi Konsumen Atas Risiko Makanan dan Kemasan Oleh Penyedia Bisnis Jasa Makanan Selama Pandemi Covid-19 - Soraya, Deasy; Arfah, Aryati; Arif, Muhammad (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
The purpose of this study is to observe the different risk perceptions of consumers towards food service business providers during the Covid-19 pandemic in Kota parepare based on differences in education level, gender and generation (age), because people today are also still ambiguous and confused about the truth of the information received regarding the spread of covid-19 both through food and food packaging. This study uses descriptive quantitative data analysis method with non- probability sampling method with purposive sampling technique & quota sampling with adjusted criteria. The sample were 162 respondents who were users of delivery applications (Grab/Gojek/Shoppe Food), had eaten at restaurants during the pandemic, had used drive thru, had shopped independently and had eaten raw foods such as sushi, during October – December 2022). The results showed that there were significant differences in consumer perceptions of food and packaging risks by age, education level and gender